Postwar Growth in Western Europe: A Re-Evaluation - Cornwall, John (The Review of Economics and Statistics, 1968)
T HE postwar growth performance of several European economies has been the cause of coincident feelings of awe, guilt, and envy. It has also been the reason for a number of attempts to explain what has allowed, say, the Germans, French, and Italians to go merrily on their way with only minor interruptions of remarkable growth records, while others, such as the British, have been faced with little other than stagnation. The studies have varied a good deal in the level of sophistication and abstraction, as well as in the relative weight given to empirical in contrast to theoretical considerations. Nevertheless, a common theme is the profound importance of capital formation as a source of growth. Neither of the two recently published studies is an exception, although the heavy weight given to capital formation in one is certainly inadvertent.' Each book is important in its own right, and together they provide an excellent opportunity to examine the main trends in an important and growing body of literature. Therefore, though emphasis will be on the two latest contributions in this area, we will include other studies for comparison and contrast. Together, they provide a sharp contrast to much current analysis which downgrades the importance of capital formation as a source of growth.